Da'wah Strategy of Nahdlatul Ulama's Fatayat PAC Management in Strengthening the Role of Women - Yuwafik, Muhammad Hamdan; Masty, Kuffa Meldana (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2025)
This study examines the da'wah strategy employed by PAC Fatayat NU in Wonodadi District, Blitar Regency, in an effort to empower women. The primary issue is the underrepresentation of women in social, economic, and religious spheres. The focus of this study is to describe the da'wah strategy and its implementation form in empowering women through religious organizations. The method employed is qualitative descriptive analysis, incorporating the theory of da'wah strategy from Abu Al-Fath Al-Bayanuni. Data were obtained through observation, interviews, and documentation. The results of the study revealed three da'wah strategies: a sentimental strategy (recitation of the Qur'an, routine religious studies, istighosah, and IHF community), a rational strategy (work meetings, socialization, and discussion of women's issues), and a sensory strategy (entrepreneurship skills training and social activities). This strategy is effective in increasing the active role of women in society and demonstrates that empowerment-based da'wah can create participatory spaces and foster social transformation.